Post-Induction Remission Status in B-Acute Lymphoblastic Leukemia Patients (B-ALL), Experience at Tertiary Care Hospital - Ilyas, Sumaira; Robert, Helen Mary; Hussain, Zahoor; Ali, Intzar; Wahid, Ayesha; Zafar, Zara (Pakistan Armed Forces Medical Journal, 2025)
Objectives: To determine the frequency of post-induction remission status and its association with cytogenetic and molecular abnormalities in patients with B-ALL. Study Design: Cross-sectional Analytical study. Place and Duration of Study: Armed Forces Institute of Pathology, Rawalpindi Pakistan, from May to Oct 2023. Methodology: A total of 112 patients who fulfilled the selection criteria were enrolled after written informed consent. All patients underwent cytogenetic and molecular assessment. Patients were treated using regimen-A for standard risk patients and Regimen-B for high-risk patients, in accordance with the UKALL 2011 guidelines. On day 29 of induction treatment, bone marrow was taken once more, post-induction remission was evaluated, and the results were statistically analyzed. Results: The mean age of the patients was 5.72+3.48 years. Post-induction remission achieved in 93(83%) patients and was significantly associated with no cytogenetic abnormality (p=<0.01), hyperdiploidy (p=0.027) and t(9;22) (p=0.003), with no molecular abnormality (p=0.038) and mutation in BCR-ABL1 (p=<0.01). Conclusion: Post-induction remission rate was 83% in B-ALL patients. There was significant association of hyperdiploidy with post induction remission; whereas majority patients t(9;22) and BCR-ABL1 failed to achieve post-induction remission.